Gas Emission Prediction for Environmental Sustainability via Heterogeneous Data Sources Correlation with Support Vector Regression - Chen C.P.; Tiong S.K.; Koh S.P.; Chooi Albert F.Y.; Mohd Yapandi M.F.K. (Institute of Electrical and Electronics Engineers Inc., 2023)
Air pollution control equipment; Artificial intelligence; Combined cycle power plants; Environmental Protection Agency; Forecasting; Gas turbines; Land use; Meteorology; Monitoring; Regression analysis; Sulfur dioxide; Sustainable development; Vectors; Combined cycle gas turbine; Emission monitoring system; Environmental sustainability; Heterogeneous data sources; Intelligent environment; Power plant parameters; Prediction performance; Support vector regression (SVR); Big data